Numerical Comparison by using Some Criteria to Estimate the Two Parameters of the Exponentiated Exponential Distribution - Mohammed, Sahar Ahmed (Iraqi Journal of Science, 2024)
The present paper shows a numerical comparison by using the number of the following criteria: mean squared, root mean Square, mean absolute, and relative mean squared error values between the methods, namely maximum likelihood and Bayesian estimators for the two parameters of the exponentiated exponential distribution. In estimating the maximum likelihood, The equations cannot be solved directly, Then Newton-Raphson method is used. Because of Bayes estimators under scale invariant squared and weighted composite linear-exponential loss functions the ratios cannot be simplified in a closed form. So, we use Lindley approximation. MATLAB program is used to display the results.